Flavor phenomenology of light dark vectors - Eguren, Jordi Folch; Klingel, Sophie; Stamou, Emmanuel; Tabet, Mustafa; Ziegler, Robert (Journal of high energy physics, 2024)
Light dark matter with flavor-violating couplings to fermions may be copiously produced in the laboratory as missing energy from decays of SM particles. Here we study the effective Lagrangian of a light dark vector with generic dipole or vector couplings. We calculate the resulting two-body decay rates of mesons, baryons and leptons as a function of the dark vector mass and show that existing experimental limits probe UV scales as large as 1012 GeV. We also derive the general RGEs in order to constrain the flavor-universal UV scenario, where all flavor violation arises radiatively proportional to the CKM matrix.
Gesehen am 23.07.2025